Physical and physiological demands of U-19 basketball refereeing: Aerobic and anaerobic demands. Issue 2 (2nd April 2016) - Nabli, Mohamed Ali; Ben Abdelkrim, Nidhal; Castagna, Carlo; Jabri, Imed; Batikh, Tahar; Chamari, Karim
ABSTRACT: Objectives : This study aimed to examine the physical and physiological demands of basketball refereeing. Methods : 16 elite-level basketball referees were studied during U-19 basketball games (n=8) for time-motion analyses, exercise heart rates (HR) and blood lactate concentration [La]. Game activities were considered as time spent and distance covered in five locomotors activities (standing, walking, jogging, running and sprinting). Results : Referees spent more time (p<0.01) walking (63.72±2.02 min) than jogging (3.10±0.29 min), running (4.24±0.46 min) and sprinting (1.69±0.24 min). Referees covered more distance (p<0.01) walking than jogging, running and sprinting across the quarters (Q). Mean HR (74.89±6.86 %HRmax ) was not significantly different across the game Q (Q1 to Q4) and halves. [La] did not show significant changes (p=0.221) when comparing the half-time (4.30±3.92 mmol.L −1 ) and the end of the game (6.70±4.90 mmol.L −1 ). Conclusion : In light of this study, we conclude that U-19 basketball refereeing is a moderate intensity activity where referees spent 81% of total game time at low-intensity with bouts of high-intensity activities throughout the game.